Anda di halaman 1dari 12

reed (jhr977) HW02 meth (55185) 1

This print-out should have 24 questions. Find the solution of the exponential equa-
Multiple-choice questions may continue on tion
3
the next column or page find all choices 34x = 9 2 x+9.
1. x = 18 correct
001 10.0 points
Determine which, if any, of the following
2. x = 9
x
f (x) = 25 + 10 ,
3. x = 18
g(x) = 52x+2 ,
h(x) = 25 (25x ) , 4. none of these
define the same function.
5. x = 9
1. only g, f
Explanation:
2. none of f, g, or h By properties of exponents,
3
3. only g, h correct 9 2 x+9 = 33x+18 .

5. only f, h 34x = 33x+18 ,

Explanation: which after taking logs to the base 3 of both
By the Laws of Exponents, sides becomes
f (x) = 25x + 10 = (52 )x + 10
4x = 3x + 18.
2x
=5 + 10 ,
Rearranging and solving we thus find that
2x+2
while g(x) = 5 and
x = 18 .
x 2 2 x
h(x) = 25 (25 ) = (5 )(5 )

= (52 )(52x ) = 52x+2 . 003 10.0 points

Thus g and h define the same function. On If a, b are the solutions of the exponential
the other hand, equation
f (0) = 11 , g(0) = 25 = h(0) , 2
3x = 93x+8,
so neither g nor h can define the same function
as f . Consequently calculate the value of ab.

1. ab = 4
only g, h

002 10.0 points 3. ab = 16

reed (jhr977) HW02 meth (55185) 2
are equivalent to
4. ab = 8
2x = 25y , 25x = 24(y+2) .
5. ab = 6 Now set v = 2x and u = 2y . Then
Explanation: v = u5 , v 5 = 256u4 .
By properties of exponents,
Substituting for v in the second equation we
93x+8 = 36x+16 . thus get
Thus the equation can be rewritten as 8
u25 = 256u4 , i .e., u = 2 21 .
2
3x = 36x+16 , Consequently, since u = 2y ,
which after taking logs to the base 3 becomes 8
y = .
21
x2 = 6x + 16.

This equation factors as 005 10.0 points

(x 2)(x + 8) = 0,
Which function has
and so its solutions are 2, 8. Hence
4
ab = 16.
2
004 10.0 points

Find y when 4 2 2 4

2x = 32y , 32x = 16y+2 . 2

1 4
1. y =
3
2 as its graph?
2. y =
7
1. f (x) = 2 3x correct
10
3. y =
21 2. f (x) = 2x1 2
8
4. y = correct 3. f (x) = 2 2x1
21
3 4. f (x) = 3x 3
5. y =
7
5. f (x) = 2x1 3
Explanation:
The equations
6. f (x) = 3x 2
2x = 32y , 32x = 16y+2 Explanation:
reed (jhr977) HW02 meth (55185) 3
The given graph has the property that

lim f (x) = 2 . 4
x

But 2

lim 2x = 0 = lim 3x , 3.
x x 4 2 2 4
while 2

lim 2x = 0 = lim 3x , 4
x x

2 3x , 2 2x1 . 4

On the other hand, the y-intercept of the 2

given graph is at y = 1.
Consequently, the graph is that of 4.
4 2 2 4
f (x) = 2 3x . 2

4
006 10.0 points

4
Which of the following is the graph of

f (x) = 2 2x1 ? 2

5.
4 2 2 4
4
2
2
4
1. correct
4 2 2 4
2 4

4 2

6.
4 2 2 4
4
2
2
4
2.
4 2 2 4
2 Explanation:
Since
4 lim 2x = 0 ,
x
reed (jhr977) HW02 meth (55185) 4
we see that and get a linear equation in x.
Consequently,
lim f (x) = 2 ,
x
3
in particular, f has a horizontal asymptote x(4 (4)) = 6 , i .e., x = .
4
y = 2. This eliminates all but two of the
3
graphs. On the other hand, f (0) = , so the
2
y-intercept of the given graph must occur at keywords: ExponentFunc, Exponent-
3
y = . FuncExam,
2
Consequently, the graph is of f is
008 10.0 points
4 If the graph of f is
10
2 9
8
7 8
6
5
4 2 2 4 4
3 4
2 2
1
0
-1
4 -2 8 4 4 8
-3
-4
-5 4
-6
007 10.0 points -7
-8
If x satisfies the equation -9 8
-10
24x = 432x ,
which of the following is the graph of f 1(x)?
determine the value of x. 10
9
8
1 7 8
1. x = 1. 65
2 4
3 4
2
2. x = 1 1
0
-1
-2 8 4 4 8
3 -3
3. x = correct -4
-5 4
4 -6
-7
5 -8
4. x = -9 8
8 -10
10
9
7 8
8
5. x = 7
8 2. 65 correct
4
Explanation: 3 4
2
Since 4 = 22 , the equation can be rewritten 1
0
as -1
-2 8 4 4 8
24x = 22(32x) , -3
-4
-5 4
so that we can now compare exponents: -6
-7
-8
-9 8
4x = 2(3 2x) -10
reed (jhr977) HW02 meth (55185) 5
10
10 9
9 8
8 7 8
7 8 6
3. 65 5
4
4
3 4 3 4
2 2
1 1
0 0
-1 -1
-2 8 4 4 8 -2 8 4 4 8
-3 -3
-4 -4
-5 4 -5 4
-6
-7 -6
-8 -7
-9 8 -8
-10 -9 8
-10
10
9
8
7 8 009 10.0 points
4. 65
4
3 4
2
1 Which of the following functions will fail to
0
-1 have an inverse?
-2
-3
8 4 4 8
-4
-5 4
-6
-7 5
-8
-9 8 4
-10 4
1.3
2
10 1
2
9
8 0
7 8 -1
5. 65 4 2 2 4
-2
4 2
3 4 -3
2 -4
1 4
0 -5
-1
-2
-3
8 4 4 8
-4 4
-5 4 4
-6
-7 2.3 correct
-8 2
-9 8 1
2
-10
0
9 -1 4 2 2 4
8 -2
7 8 2
6. 65 -3
4 -4
3 4 -5
4
2
1
0 5
-1 4
-2
-3
8 4 4 8 4
-4 3.3
-5 4 2
-6 1
2
-7
-8 0
-9 8
-10 -1 4 2 2 4
-2
-3
2
Explanation: -4
4
The graph of f 1 (x) is obtained by reflect- -5
ing the graph of f over the line y = x:
reed (jhr977) HW02 meth (55185) 6
5
4
4 Explanation:
4.3 Since f (7) = 8 and f is one-to-one, the
2 inverse, f 1 , of f exists and
1
2
0
-1 f 1 (f (x)) = f (f 1(x)) = x .
4 2 2 4
-2
-3
2 Consequently,
-4
-5
4
5 f 1 (8) = f 1 (f (7)) = 7 .
4
4
5.3
2
1
2
0
keywords: inverse, one-to-one,
-1 4 2 2 4
-2 011 10.0 points
-3
2
-4 Determine the inverse function, f 1 , of f
-5
4
when
Explanation:
If a function f has an inverse, then it must f (x) = 3x , (x 0) .
be a one-to-one function; equivalently, the
graph of f must pass the horizontal line test. 1 2
The only graph failing to pass this test is 1. f 1(x) = x , ( < x < )
3

4
4 2. f 1(x) does not exist
3
2
1
2 1 2
3. f 1(x) = x , (x 0)
0 3
-1 4 2 2 4
-2 1 2
2 4. f 1(x) = x , (x 0) correct
-3 3
-4
-5
4 1
5. f 1(x) = x2 , (x 0)
3
010 10.0 points
Explanation:
If f is a one-to-one function such that The function f (x) = 3x is a one-to-one
f (7) = 8, what is the value of f 1(8)? function for x 0; hence the inverse f 1(x)
exists. Now the solution to the equation
1. f 1 (8) = 11

3x = y , y > 0
2. f 1 (8) = 3
1
3. not enough information given is x = y 2 . But the original function f (x)
3
can take only non-negative values, i.e., the
4. f 1 (8) = 7 correct range of f is [0, ); this means that the
domain of f 1 is [0, ). Consequently,
5. f 1 (8) = 4
1 2
1 f 1 (x) = x , (x 0 ) .
6. f (8) = 9 3
reed (jhr977) HW02 meth (55185) 7

012 10.0 points 5. log10 8 = 2

Find the inverse of
Explanation:
1 + 4x Taking logs to the base 2 of both sides we
f (x) = .
7 5x see that
7x + 1 log2 8 = log2 23 = 3 log2 2.
1. f 1 (x) =
5x + 4
7x 1 But log2 2 = 1, so
1
2. f (x) = correct
5x + 4
log2 8 = 3 .
1 7x 1
3. f (x) =
4x + 5
7x + 1
4. f 1 (x) = keywords: LogFunc, LogFuncExam,
4x + 5
4x 1 014 10.0 points
5. f 1 (x) =
5x + 7 Use properties of logs to simplify the ex-
Explanation: pression
To determine the inverse of f we first solve p p
for x in log9 (x x2 27 ) + log9 (x + x2 27 ).
1 + 4x
y = .
7 5x
In this case 1. log9 3
7y 1
x = . 2. 9 + log9 3
5y + 4

The inverse f 1 is now obtained by inter- 3. 1 + log9 3 correct

changing x, y. Thus
4. 1 + log3 9
7x 1
y = f 1(x) = . 5. log3 9
5x + 4
Explanation:
013 10.0 points By properties of logs the given expression
Rewrite can be rewritten as
23 = 8 h p p i
log9 (x x2 27 ) (x + x2 27 )
in equivalent logarithmic form.
 p 2 
2
1. log8 2 = 3 = log9 x x2 27 = log9 27 .

2. log2 8 = 3 But
log9 27 = log9 9 + log9 3 .
3. log2 8 = 3 correct Thus the given expression reduces to

1 1 + log9 3 .
4. log2 = 3
8
reed (jhr977) HW02 meth (55185) 8

keywords: LogFunc, LogFuncExam, 5

4. x =
4
015 10.0 points 13
5. x =
Find the value of x when 12
1 Explanation:
x = 5 log3 + 6 log4 64 . Since
9
1
1. x = 9 7log7 x = x, 8 log8 x = ,
x

2. x = 10 we see that

7log7 2 = = 2,
3. x = 10
while
4. x = 9 1
8 log8 4 = = .
4
5. x = 8 correct Consequently,

6. x = 8 7 5 13
x = = .
Explanation: 3 4 12
By properties of logs,
1  1  017 10.0 points
log3 = log3 = 2,
9 (3)2 Find the value of x when
   
while x = 6 log6
2
63 3 log3
3
32 .
log4 64 = log4 (4)3 = 3 .
1. x = 7 correct
Consequently,
41
x = 18 10 = 8 . 2. x =
6
13
3. x =
016 10.0 points 2

Find the value of x when 20

4. x =
3
7  log7 2   
x = 7 5 8 log8 4 43
6 5. x =
6
without using a calculator.
Explanation:
13 Since
1. x = correct
12
r loga z = loga z r , loga a = 1,
7
2. x =
6 we see that
7   3
2
3. x = log6 63 = ,
6 2
reed (jhr977) HW02 meth (55185) 9
while  
3 2 3. f (x) = e41
log3 32 = .
3
Consequently,
4. f (x) = x5
x = 7 .
5. f (x) = 8x

018 10.0 points Explanation:

By the property of inverse functions,
Use properties of logs to simplify the ex-
pression 5log5 y = y, eln y = y .
 
2 2 1 Consequently,
loga (32) + loga (16) loga (8) + loga 7
5 5 25
f (x) = 58(log5 e) ln x = (5log5 e )8 ln x
as much as possible. .
ln x8 8
= e = x
1. loga (64)
020 10.0 points
2. loga (32)
Which one of the following could be the
3. 16 graph of

f (x) = log2 (3 x)
4. loga (16) correct
when dashed lines indicates asymptotes?
6

5. loga 2

Explanation: 1.
By properties of logs the given expression 2
can be rewritten as

2
! 2 4
25 16 5
loga 2 2 = loga (16) .
85 2 25 2

Simplify the expression 2

2.
f (x) = 58(log5 e) ln x

as much as possible. 2 4

1. f (x) = x8 correct 2

2. f (x) = x40
reed (jhr977) HW02 meth (55185) 10
other hand, log2 (x) is defined only on (0, )
and
3. 2

lim log2 (x) = , lim log2 (x) = ,

x 0+ x
2 4
so x = 0 is a vertical asymptote. Thus the
2 graph of log2 (x) is

2
4. 2

2 4 2 4

2
2

5. correct
2 To get the graph of log2 (x) we simply flip
the one for log2 (x) over both the x-axis and
the y-axis, producing
2 4

2
6.
2
4 2

2 4
2
2

Explanation: To obtain the graph of y = log2 (3 x)

Lets first review some properties of log2 (x) from this last one all we have to do now is
and log2 (x). Since log2 (1) = 0, the graph translate horizontally to the right by 3, pro-
of log2 (x) has x-intercept at x = 1. On the ducing
reed (jhr977) HW02 meth (55185) 11
Consequently,

5
x = ln(2) .
2 2

2 4
022 10.0 points

ln(x) + ln(x + 2) = ln(15) .

keywords: LogFunc, LogFuncExam,
1. x = 6
021 10.0 points
Solve for x when
2. x = 5
1
e2x = .
32 3. none of these correct

1. x = 10 ln(5)
4. x = 6
5
2. x = ln(2) correct
2 5. x = 5
5
3. x = ln(2) Explanation:
2 Since the domain of ln(x) is (0, ), we take
x > 0. Now by properties of logs,
4. x = 5 ln(5)
 
x(x + 2)
ln(x) + ln(x + 2) ln(15) = ln
5. x = 5 ln(5) 15
 2 
x + 2x
6. x = 10 ln(2) = ln .
15
Explanation:
But then
Taking logs of both sides we see that x2 + 2x
= 1.
15
 
2x 1
ln(e ) = ln .
32 Thus x is the positive solution of the equation

Thus x2 + 2x 15 = (x + 5)(x 3) = 0 .
 
1
ln = 2x ln(e) = 2x . Consequently,
32
Now x = 3 .
 
1 
ln = ln 25 = 5 ln(2) .
32 023 10.0 points
reed (jhr977) HW02 meth (55185) 12
If a, b are the solutions of the equation
2. f 1(x) = ln(3 x) , x < 3
3 ex + 2 ex = 7,
 1 
find the value of a + b. 3. f 1 (x) = ln , x < 3 correct
3x
7
1. a + b = 4. f 1(x) = ln(x 3) , x > 3
3
2 1
2. a + b = ln correct 5. f 1(x) =
3 3 + ex
7
3. a + b = e 3  1 
1
6. f (x) = ln , x > 3
x3
2
4. a + b = ex
3 7. f 1(x) =
3 + ex
7 ex
5. a + b = ln 8. f 1(x) =
3 3 + ex
Explanation: Explanation:
Set u = ex in the given equation. Then it As ex is defined and decreasing for all x,
becomes the inverse f 1 exists because f is increasing;
2
3u + = 7 in addition, since ex > 0, we see that
u
and finally a quadratic equation domain(f ) = (, ) ,
3u2 7u + 2 = 0. range(f ) = (, 3) ,
But after factorization, so by properties of inverse functions,
3 u2 7 u + 2 = (u 2)(3u 1). domain(f 1 ) = (, 3) ,
Thus range(f 1) = (, ) .
a b 1
e = 2, e = ,
3
i.e. To determine f 1 we first solve for x in
1
a = ln 2, b = ln . y = 3 ex :
3
Consequently, ex = 3 y , i .e., x = ln(3 y) .
2 Reversing now the roles of x and y we thus
a + b = ln .
3 get
 1 
024 10.0 points f 1 (x) = ln , x < 3,
3x
Find the inverse, f 1, of since
1
f (x) = 3 ex . ln x = ln .
x

1
1. f 1 (x) =
3 + ex